2013
DOI: 10.1016/j.jaut.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis is associated with signaling alterations in naturally occurring autoreactive B-lymphocytes

Abstract: Immune tolerance established during the development of B lymphocytes can be subverted in mature cells and lead to autoimmunity. This study focuses on the recently discovered subset of CD19+CD27−IgD+IgMlow/− B cells that recognize self-antigens and have the capacity to produce autoantibodies, but under normal conditions do not generate autoimmune response due to intrinsic signaling inhibition (a condition known as clonal anergy and characterized by impaired antigen receptor signaling). Phosphorylation of intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…However, RA subjects exhibited substantially increased phosphoprotein responses to BCR stimulation in the CD19 + CD27 − IgD + IgMl low/− B cell subset, as compared to normal controls (total pTyr mean±SE % increase of 121.4±30.6 vs. 22.5±31.0 in RA and control groups, respectively (p = 0.05)), suggesting that the breach of PIT in RA patients occurs regardless of the age (data previously reported [2]). …”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, RA subjects exhibited substantially increased phosphoprotein responses to BCR stimulation in the CD19 + CD27 − IgD + IgMl low/− B cell subset, as compared to normal controls (total pTyr mean±SE % increase of 121.4±30.6 vs. 22.5±31.0 in RA and control groups, respectively (p = 0.05)), suggesting that the breach of PIT in RA patients occurs regardless of the age (data previously reported [2]). …”
Section: Introductionsupporting
confidence: 66%
“…We have established the loss of PIT in autoreactive B ND cells as a contributing factor in the development of RA and demonstrated that inhibitory BCR signaling cascades involved in the maintenance of PIT are altered in RA [2]. According to the central hypothesis of our study (Figure 1), in healthy individuals, autoreactive B ND cells that have escaped the mechanisms of central tolerance maintain the peripheral immune tolerance (PIT) to ubiquitous autoantigens through continuous receptor tuning and BCR signaling inhibition, and our results demonstrate that this tolerogenic mechanism is compromised in RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoreactive lupus B cells with an anergic phenotype could have an abnormally prolonged lifespan, being neither activated nor deleted (23). Of interest, a loss of anergy in T3 B cells has been observed in autoimmune diseases such as collageninduced arthritis and rheumatoid arthritis (24)(25)(26), suggesting that the generation and survival of anergic B cells requires a fine control to avert autoimmunity. 2+ flux was measured after BCR stimulation in NZB/W mice (dark gray) and in CW controls (light gray).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of ARD is unknown. Dysregulation of innate and adaptive immunity [2], breaking of tolerance [3][4][5], production of autoantibodies [6][7][8][9], and generation of autoreactive T and B cells [10][11][12], lead to necrosis, scaring, and organ dysfunction and account for many of the clinical manifestations of ARD [13,14]. Due to the complexity of the pathogenesis, there is no universal therapeutic approach that is effective for all cases of ARD.…”
Section: Introductionmentioning
confidence: 99%